2002
DOI: 10.1002/ps.467
|View full text |Cite
|
Sign up to set email alerts
|

Fate of spinosad in litter and soils of a white spruce plantation in central Ontario

Abstract: Spinosad is a natural insecticide with potential as a novel biorational control agent for spruce budworm (Choristoneura fumiferana [Clem]), the most destructive insect defoliator of spruce and balsam fir in Canada. Concurrent terrestrial fate experiments were conducted under full coniferous canopy and in a natural opening of a mature white spruce (Piecea glauca [Moench]) plantation of central Ontario to examine the fate and persistence of spinosad in the forest floor and underlying soils. Mean initial residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Very short half-lives values (<1 day) for spinosad was observed in agricultural soils of the southern USA [Hale and Portwood, 1996]. Thompson et al [2002], found that spinosad is quickly metabolized by soil microorganisms under aerobic condition, however, under anaerobic conditions, the degradation is slower. The results obtained by Gębala and Mickiewicz [2012] shown that spinosad is not ready biodegradable in water and not toxic to microbial inoculum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very short half-lives values (<1 day) for spinosad was observed in agricultural soils of the southern USA [Hale and Portwood, 1996]. Thompson et al [2002], found that spinosad is quickly metabolized by soil microorganisms under aerobic condition, however, under anaerobic conditions, the degradation is slower. The results obtained by Gębala and Mickiewicz [2012] shown that spinosad is not ready biodegradable in water and not toxic to microbial inoculum.…”
Section: Resultsmentioning
confidence: 99%
“…Although such compounds tend to be water soluble, easily metabolized and non-bioaccumulatory, biogenic sourcing does not necessarily confer environmental acceptability [Thompson et al, 2000]. Therefore, assessment of environmental persistence, fate and toxicological properties, including stud-ies, is necessary for these compounds [Thompson et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…127,128 Spinosyns also did not show a lengthy persistence in soil and litter, presumably in large part due to facile degradation by soil organisms. [128][129][130][131] Spinosyns have also been found to undergo facile metabolism in several mammals and fowl. 18,132 Overall, the spinosyns are readily subject to a number of diverse degradative pathways and metabolic mechanisms that reduce their persistence in plants, animals and the environment.…”
Section: Semisynthetic Derivatives and Sarmentioning
confidence: 99%
“…Previous studies on the environmental fate of spinosad focused on the degradation of spinosad in aqueous systems (Cleveland et al, 2002a;Liu et al, 2005), and assessment of the ecological risk of spinosad application on cotton and white spruce (Thompson et al, 2002a(Thompson et al, , 2002bCleveland et al, 2002b). The purpose of the present work was to study the dissipation rate and ultimate residue of spinosad in an eggplant field ecosystem, and thereby provide an evaluation for scientific, safe use of spinosad.…”
mentioning
confidence: 99%